Small bowel bleed: The forgotten complication of chronic myeloid leukemia - Agrawal, Jatin Bankeylal; Yadav, Manjusha; Purohit, Kartik; Vanik, Sangeeta (Indian Journal of Case Reports, 2025)
Chronic myeloid leukemia (CML) is a clonal bone marrow stem cell disorder with proliferation of granulocytes and their precursors. Gastrointestinal (GI) involvement is uncommon across all types of leukemia. It typically occurs during the blast phase or in cases of acute leukemia. However, advancements in treatment have significantly reduced the incidence of such complications. We present a unique case of a small bowel bleed in a 68-year-old patient of CML who presented with recurrent massive lower GI bleed.